Comparative analysis of two techniques to evaluate the water storage capacity in Chuquiraga erinacea Don (Semiárida, 2018)
Rainfall interception is a process scarcely studied in arid and semiarid environments. The aim of this study was comparatively analyze two field techniques to evaluate the water storage capacity in Chuquiraga erinacea Don., characteristic shrub species of the CaldenalMonte Occidental ecotone region, Argentina The study was conducted in the annexed field of INTA in Chacharramendi, La Pampa. Water storage capacity was measured on whole plants from two techniques on field: rainfall simulation and immersion. Water storage capacity, expressed in percentage of biomass was determined by difference wet weight fresh weight. Equality of results from field techniques for whole plants of Chuquiraga erinacea justified the application of immersion method in the study to be more expeditious implementation and more economical in terms of time and costs.
Keywords: rainfall interception; immersion; rainfall simulation; biomass; semiaridarid